PEMANFAATAN TRICHODERMA SP SEBAGAI AGENS HAYATI UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN DI DESA PUDAK KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI - Dedy Antony; Lizawati Lizawati; Weni Wilia; Yulia Alia (Universitas Negeri Medan, 2023)
Pudak Village, Kumpeh Ulu District, is one of the rice producers in Muaro Jambi Regency, with a paddy field area of up to 180 ha. Even so, there are obstacles that often-become inhibiting factors for farmers to increase rice production. One of them is the problem of fertilizer which is always difficult for farmers in almost every growing season, besides that the attack of plant-disturbing organisms also becomes a barrier for farmers to get optimal results.Utilization of agricultural wastes such as remaining rice straw, husks, household organic waste can be an alternative that can reduce the use of synthetic fertilizers, because they are easy to obtain, inexpensive, environmentally friendly, and economical in production costs. Making compost and pesticides with active ingredient Trichoderma sp. is one of the decomposers used to utilize organic wastes around homes and agricultural land.Public service activities can increase farmers' knowledge about biological agents or antagonistic microorganisms in the form of the fungus Trichoderma sp. The method used is in the form of counseling on how to get the fungus Trichoderma sp. around farmers' land, the benefits of these antagonistic fungi are both as biological agents and decomposers, propagation techniques for application in the field. and how to apply it to rice plants. This PPM activity was able to increase farmers' knowledge about the benefits of the fungus Trichoderma sp. Apart from being a decomposer, it can also be used as a biological agent to control pests and plant diseases and can support environmentally friendly and sustainable agriculture. Keywords: Antagonistic Fungi; decomposer; Trichoderma sp.; Biological Agents